Confiabilidad intraclase del Test de Fiabilidad del Sistema Neruromotor del Bebe de Harris en lengua portuguesa: aplicación con niños brasileños - Grazielle Roberta Freitas da Silva; Maria Vera Lúcia Moreira Leitão Cardoso (Universidad de Alicante, 2012)
Objective: to evaluate the reliability interrater to characterize the profile of children and his caregivers using the first part of the Harris Infant Neuromotor Test(HINT) into Portuguese idiom. Methods: Methodological and longitudinal study, convenience sample composed by 73 children and her caregivers attended in an public institution in Fortaleza-Ceará-Brazil from September 2007 to September 2008. Results: The reliability interrater at first assessment baby was between 0,501 and 1,000, only two items showed low concordance. Sixteen items showed reliability 100% on third assessment. The concordance of the total score showed a value of 0,801 (p= 0,001) and 0,898 (p= 0,001) on first and third assessment, respectively.Conclusions: HINT is a reliable test for the sample researched, however it need be improved aiming represent all children of the Brazilian Nation. Objetivo: avaliar a confiabilidade interclasse usando a primeira parte do Harris Infant Neuromotor Test na língua portuguesa. Métodos:Estudo metodológico, longitudinal, com amostra por conveniência composta por 73 crianças e seus responsáveis atendidos numa instituição pública em Fortaleza-Ce-Brasil, de setembro/2007 a dezembro/2008. Resultados:A confiabilidade interclasse, na primeira avaliação da criança variou entre 0,501 e 1,000, apenas dois itens apresentaram baixa concordância. Na terceira, 16 itens apresentaram 100% de confiabilidade. A concordância do escore total apresentou valor de 0,801 (p= 0,001) e 0,898 (p= 0,001) na primeira e terceira avaliação, respectivamente. Conclusões: O HINT apresentou- se confiável para a amostra estudada, mas necessita ser aprimorado para representar todas as crianças brasileira.